Organisational Culture Characterisation of Construction Firms in Nigeria - Bamgbade, Adebisi Abosede; Jimoh, Richard Ajayi; Oyewobi, Luqman Oyekunle; Anifowose, Maroof (UI Scholars Hub, 2020)
Organisational culture characterisation is indispensable for aspiring organisations that want to measure up with the contemporary business trend in terms of performance. This paper aims to determine the organisational culture characterisation of construction firms in Nigeria to improve the organisational culture power to drive organisational performance of the firms. Thus the objectives are to enumerate the factors that contribute to the organisational culture capability and to determine the organisational culture characterisation of construction firms in Nigeria. A quantitative method was adopted for this research in which 113 questionnaires from a sample size of 254 disseminated informed by purposive random sampling technique, were used to draw the data from the respondents who are predominantly construction workers. The analysis of the data was done using factor analysis, k-mean analysis, and a one-way ANOVA. The results reveal that there is the presence of three distinct organisational culture clusters in the construction firms in Nigeria. The results also disclosed that family and work policy should be inculcated into the organisational culture and held in regard if performance is inevitable. The study concluded that organisational culture is a vital aspect of construction firms and each firm should improve on their culture to better their organisational performances. It is recommended that family and work policy should be given preference in the organisation, also supervisors should be trained in relevant skills that will aid their commitment to their workforce diversity.